Welcome in mental health in primary health care in the context of the COVID-19 pandemic (Research, Society and Development, 2021)
Objective. Analyze, in the scientific production, reception in mental health in primary health care in the context of the COVID-19 pandemic. Methodology. Full articles from the Medical Publications (PubMed) and Latin American and Caribbean Health Sciences (LILACS) databases were used. For the search, the following keywords were used: "Mental Health Assistance", "Mental Health", "Family Health Strategy", "Unified Health System", "Health Personnel", "User Embracement" and "COVID-19"; obtained according to the Health Sciences Descriptors (DeCS), having as Boolean operators “AND/AND” and “OR/OR”. After applying the inclusion criteria defined, 15 articles were selected for review. Results. All the articles selected for this review addressed the Family Health Strategy's action strategies in the context of mental health care, both before and during the pandemic period. In addition, many studies also brought limitations such as difficult access, low resolution in primary care, lack of professional qualifications, in addition to lack of internet access by users and low adherence to new approaches in the context of the pandemic. Conclusion. It can be concluded that there is an implementation of new practices that adapt to the new scenario, such as teleservice, through video calls and calls. Despite this, these practices have limitations due to the profile of the users. Thus, new welcoming strategies are needed that can include all service users.